A new Patagonian species of Cricosaurus (Crocodyliformes, Thalattosuchia): first evidence of Cricosaurus in Middle–Upper Tithonian lithographic limestone from Gondwana - Herrera, Yanina (2013)
Upper Jurassic (Tithonian) deposits in north-western Patagonia, Argentina, have yielded rich and taxonomically diverse assemblages of marine reptiles. These assemblages are also remarkable by their quality of preservation and are represented by ichthyosaurs, plesiosaurs, turtles and crocodyliforms. Despite the abundant crocodyliform record, only two metriorhynchid taxa have been identified: Cricosaurus araucanensis and Dakosaurus andiniensis. Here we described a new species of Cricosaurus, which represents the second species of Cricosaurus in the Tithonian of the Neuque´n Basin, and the first metriorhynchid found in lithographic limestone from Gondwana. Furthermore, this specimen has the most complete postcranial remains of any metriorhynchid from South America. The new species is characterized by a short distance between the premaxilla and the nasal, a relatively narrow interorbital width, 23–25 mandibular teeth, bicarinated teeth with fine apicobasally aligned ridges, interalveolar spaces between the first seven teeth approximately 1.5 times longer than the anteroposterior diameter of the respective alveoli. To test the assignment of the new species to Cricosaurus, we carried out two phylogenetic analyses. In both analyses, Cricosaurus lithographicus sp. nov. is nested with other species referred to this genus. This new species has peculiar enamel ornamentation, characterized by numerous, fine apicobasally aligned ridges, when compared to other species of the genus.